Elite athlete preferences for nutrition education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, Aotearoa New Zealand - Solly, Hayley (Massey University, 2022)
Background: Nutrition education (NE) has the potential to be a catalyst for athletes to optimise their diet and consequently enhance performance. However, very little research has been undertaken to understand what athletes would like in a nutrition education programme (NEP). The present study aimed to investigate the preferences of elite athletes for a NEP with a specific focus on preferences for pedagogy, content, format, and facilitator. Methods: Athletes (n=124, median (IQR)=22 (9) years, female 54.8%) competing at a national or international level from 22 sports, and living in New Zealand (n=101, 81.5%) and Australia (n=19, 15.3%) participated in an online survey developed by the researchers. Responses (from descriptive Likert scales, ranking of preferences, single and multiple answer multi-choice questions) were analysed using descriptive statistics. Results: Athletes were very (45.2%) or extremely interested (37.9%) in NE and value a NEP that is engaging (96.0%) and credible (91.1%). Teaching techniques considered extremely effective for learning were life examples (47.6%), applied hands on activities (30.6%), and discussions with the facilitator (30.6%). Setting personal nutrition goals was important to most athletes (83.9%), along with two-way feedback with the facilitator (75.0%). General nutrition topics considered an essential priority for NE were energy requirements (52.4% of athletes), hydration (52.4%), and nutrient deficiencies (41.9%). Performance topics considered essential were recovery (58.1%), pre-exercise nutrition (51.6%), nutrition during exercise (50.0%) and energy requirements for training (49.2%). Adapting meals for training requirements (37.9% of athletes) and behaviour change techniques (26.6%) were considered essential nutrition-related life-skills. Credible content was important (91.1%), and most participants wanted some repetition of topics (69.4%). Athletes’ top-ranked setting preferences were ‘in person group sessions’ (mean rank 4.66), followed by a ‘mixture of in person one-on-one and group sessions’ (mean rank 4.55), and ‘one-on-one sessions’ (mean rank 4.48). For both online and in person group sessions most athletes wanted to share NE with athletes of the same sporting calibre (61.3%) and with 6-10 others (in person 44.4%, online 31.5%). Preferred session duration was 31-60 minutes (in person 63.7%, online 58.9%) and held monthly (in person 36.3%, online 38.7%). A performance dietitian or nutritionist was the top-ranked facilitator (mean rank 4.09), followed by a sports/exercise physiologist (mean rank 4.07), and an experienced athlete in the sport (mean rank 3.69). Preferred facilitator traits were credibility (73.4%), experience in sports nutrition (76.6%) and knowledge of the sport (85.5%). Conclusions: Athletes were interested in NE and valued an engaging NEP that included kinaesthetic, aural, and visual teaching techniques. Athletes preferred ‘in person group sessions’ for the delivery of NE. Preferences were that content be credible, and covered a mixture of general, performance and skills-based nutrition topics, such as adapting meals for sporting requirements. Credibility of the facilitator was important, as was experience in sports nutrition and knowledge of the athlete’s sport. Further research is needed with athletes at different levels and across all sports to further understand athletes’ preferences for NE.
Keywords: 321006 Sport and exercise nutrition